2014
DOI: 10.1002/wcc.324
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of global decarbonization scenarios: what do they tell us about feasibility?

Abstract: Dozens of scenarios are published each year outlining paths to a low carbon global energy system. To provide insight into the relative feasibility of these global decarbonization scenarios, we examine 17 scenarios constructed using a diverse range of techniques and introduce a set of empirical benchmarks that can be applied to compare and assess the pace of energy system transformation entailed by each scenario. In particular, we quantify the implied rate of change in energy and carbon intensity and low-carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 35 publications
1
122
0
Order By: Relevance
“…A similar analysis has been done by Loftus et al (2014), who normalized electricity capacity deployment rates in various global decarbonization scenarios using global GDP. In their study they found that the rates of change are broadly consistent with historical experience.…”
Section: Average Annual Capacity Additionmentioning
confidence: 91%
See 2 more Smart Citations
“…A similar analysis has been done by Loftus et al (2014), who normalized electricity capacity deployment rates in various global decarbonization scenarios using global GDP. In their study they found that the rates of change are broadly consistent with historical experience.…”
Section: Average Annual Capacity Additionmentioning
confidence: 91%
“…In their study they found that the rates of change are broadly consistent with historical experience. Only specific decarbonization scenarios with imposed restrictions on the implementation of clean and carbon sequestration technologies would lead to unprecedented rates of change for the remaining eligable low-carbon energy technologies (Loftus et al, 2014).…”
Section: Average Annual Capacity Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, even a complete decarbonization of the nation's electricity production would not be enough to meet a 2050 target of 80 per cent reduction. Most of the transport industry would have to be decarbonized as well (Loftus et al 2015), fuelled by a mix of synthetic products from a nuclear-derived surplus of heat and electricity and battery electric 'plug-in' vehicles (Brook 2012b), and current domestic gas use would have to be electrified (Heard 2013). Massive gains in efficiency might also be needed, depending on deployment rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Reference [44] categorize decarbonization scenario studies into four types of methodologies (the low-carbon technology options considered in some of these studies include carbon capture and storage and nuclear), namely (i) top-down, scenario based back-casting; (ii) top-down integrated assessment modeling; (iii) bottom-up energy system modeling; and (iv) bottom-up technical or techno-economic assessments. These methodologies typically apply cost as a cut-off criteria, otherwise the models stop with technology deployment once its desired objective (e.g., emission reduction) is reached.…”
Section: Strength and Limitations Of The Remap Methodologymentioning
confidence: 99%